2007
DOI: 10.1152/jn.00755.2007
|View full text |Cite
|
Sign up to set email alerts
|

Subdivision-Specific Responses of Neurons in the Nucleus of the Tractus Solitarius to Activation of Mu-Opioid Receptors in the Rat

Abstract: Microinjection of opioid receptor agonists into the nucleus tractus solitarius (NTS) has differential effects on cardiovascular, respiratory, and gastrointestinal responses. This can be achieved either by presynaptic modulation of inputs onto neurons or by postsynaptic activation of receptors on neurons in specific regions. Therefore we sought to determine whether responses of neurons to activation of opioid receptors were dependent on their location within the NTS. Using whole cell patch-clamp recordings from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
2
23
1
Order By: Relevance
“…However, in the present study, suppression of tonic as well as phasic GABA signaling was observed. Smith and colleagues did report an outward current with superfusion of EM-1 that they attributed to direct hyperpolarization of GABA neurons (Glatzer et al 2007), which was consistent with an earlier study (Poole et al 2007). Both studies attribute this direct hyperpolarization to the activation of postsynaptic K ϩ channels, but neither study performed additional experiments to characterize this current.…”
Section: Discussionsupporting
confidence: 80%
“…However, in the present study, suppression of tonic as well as phasic GABA signaling was observed. Smith and colleagues did report an outward current with superfusion of EM-1 that they attributed to direct hyperpolarization of GABA neurons (Glatzer et al 2007), which was consistent with an earlier study (Poole et al 2007). Both studies attribute this direct hyperpolarization to the activation of postsynaptic K ϩ channels, but neither study performed additional experiments to characterize this current.…”
Section: Discussionsupporting
confidence: 80%
“…In the NTS, m-receptors are notably located on the endings of afferent neurons from the respiratory tract and peripheral sensory receptors regulating respiration, where they inhibit activity particularly of the dorsolateral and medial regions of the nucleus [127]. Respiratory rhythm generation is coordinated by interactions between the brainstem respiratory centers in the retrotrapezoid and parafacial neuron complexes and the nearby pre-Bötzinger complex (a neuronal complex identified in rodents, but not yet characterized in man).…”
Section: Respiratory Depressionmentioning
confidence: 99%
“…High densities of endomorphin (endogenous opioid agonist) immunoreactive fibers and cell bodies have been found in the dorsal medial portion of the caudal NTS, a region where second-order neurons of the carotid body chemoreceptors are located . Anatomical data at the light and electron microscopic level and electrophysiological observations showed that opioid receptors are present at both pre-and postsynaptic sites in the dorsolateral NTS, often at the same synapse (Poole et al 2007). Thus it is possible that opioids affect the peripheral chemoreflex pathway by depressing synaptic input to the second-order neurons.…”
mentioning
confidence: 99%